THE IMPACT OF WHOLE BLOOD DONATION ON ATHLETIC PERFORMANCE - Magdalena Zięba; Szymon Rudawski; Maja Elertowicz; Kateryna Shtohryn; Hubert Gugulski; Magdalena Morytko; Mikołaj Moskwa; Patrycja Herod; Aleksandra Wójciak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Whole blood donation induces acute hematological alterations that may temporarily impair aerobic performance, particularly in athletes whose training and competition outcomes depend on maximal oxygen transport capacity. This review aims to synthesize current evidence regarding the physiological and performance-related consequences of a standard whole blood donation (450-500 mL), with particular emphasis on changes in hemoglobin concentration, hemoglobin mass, maximal oxygen uptake (VO₂max), and recovery timelines.Results: Across controlled studies published between 1990 and 2025, whole blood donation consistently reduces hemoglobin concentration by approximately 7-10% within 24-48 hours, accompanied by a 5-10% decline in VO₂max. These hematological and physiological changes result in measurable reductions in maximal exercise capacity, including decreased peak power output and shorter time to exhaustion. Submaximal exercise responses are largely preserved, suggesting that functional impairment is most pronounced at intensities near or at VO₂max. Full restoration of hemoglobin mass and maximal aerobic performance typically requires 3-6 weeks and is strongly influenced by individual iron status, donation frequency, and training load. Plasma donation, by contrast, does not appreciably affect VO₂max but may transiently alter anaerobic performance due to reduced buffering capacity.Conclusion: Whole blood donation transiently diminishes oxygen-carrying capacity and maximal aerobic performance by reducing hemoglobin concentration and total hemoglobin mass. While these effects are reversible, recovery can be prolonged in individuals with low iron stores or high endurance demands. Understanding the magnitude and time course of these changes is essential for athletes, coaches, and clinicians in planning training and competition schedules. Recognition of the physiological mechanisms involved may also guide the development of individualized donation strategies and iron management protocols for athletic populations.